Inspiring Through Creativity: Decorating Iron Railings in Phatna Witya with Used Plastic as an Example of Recycling for Students - Falasifah, Nihlatul; Ibrahim, Abdullah Malik; Dabitha, Atthaitha Allysia (Nursyam Center, 2024)
This research aims to utilize the existing assets at Phatna Witya School, especially the human resource assets, to solve the plastic waste challenges the school faces. Using the ABCD (Asset- Based Community Development) method, the research focused on an asset-based approach to develop environmental awareness among students and the school community. One activity was to recycle used plastic bottles into creative decorations for the iron railing in front of the classroom. This project is not only a tangible example of the reutilization of plastic waste, but also serves as a motivation for the entire school community to be more sensitive to the importance of maintaining cleanliness and environmental sustainability. The results showed that this activity effectively increased students' environmental awareness and encouraged them to actively contribute to creating a clean and environmentally friendly school environment